PATHOGENESIS OF THE BURN DISEASE (part 1) - Нетюхайло, Л.Г.; Kharchenko, S.V.; Kostenko, А.G. (World of Medicine and Biology, 2010)
On evidence of the literature of the native and foreign sources, in pathogenesis of the burn disease are represented and the main pathophysiological mechanisms are shown.
Keywords: burn disease; pathophysiological mechanisms